Marking Time : On the Anthropology of the Contemporary - Rabinow, Paul (Book collections on Project MUSE., 2008)
In Marking Time, Paul Rabinow presents his most recent reflections on the anthropology of the contemporary. Drawing on the work of Michel Foucault, John Dewey, Niklas Luhmann, and German painter Gerhard Richter, Rabinow offers a set of conceptual tools for scholars examining cutting-edge practices in the life sciences, security, new media and art practices, and other emergent phenomena. Taking up topics that include bioethics, anger and competition among molecular biologists, the lessons of the Drosophila genome, the nature of ethnographic observation in radically new settings, and the moral landscape shared by scientists and anthropologists, Rabinow shows how anthropology remains relevant to contemporary debates. By turning abstract philosophical problems into real-world explorations and offering original insights, Marking Time is a landmark contribution to the continuing re-invention of anthropology and the human sciences. --From publisher's description.